Symptoms of Paranoia Experienced by Students of Pakistani Heritage in England: The Role of Explicit and Implicit Identities and Perceived Discrimination. Issue 9 (5th September 2022) - Elahi, Anam; McIntyre, Jason C.; Thomas, Justin; Abernethy, Louise; Bentall, Richard P.; White, Ross G.
Abstract: Individuals belonging to ethnic minority groups are less likely to experience symptoms of psychosis, such as paranoia, if they live in areas with high proportions of people from the same ethnic background. This effect may be due to processes associated with group belonging (social identification). We examined whether the relationship between perceived discrimination and paranoia was moderated by explicit and implicit Pakistani/English identification among students of Pakistani heritage ( N = 119). Participants completed measures of explicit and implicit Pakistani and English identity, a measure of perceived discrimination, and a measure of paranoia. Perceived discrimination was the strongest predictor of paranoia (0.31). Implicit identities moderated the relationship between perceived discrimination and paranoia (−0.17). The findings suggest that higher levels of implicit Pakistani identity were most protective against high levels of paranoia (0.26, with low implicit English identity; 0.78, with medium English identity; 1.46, with high English identity). Overall, a complex relationship between identity and paranoia was apparent.